The Cambridge history of American women's literature - Bauer, Dale M., 1956- (Cambridge : Cambridge University Press, 2012)
'The field of American women's writing is one characterized by innovation: scholars are discovering new authors and works, as well as new ways of historicizing this literature, rethinking contexts, categories, and juxtapositions. Now, after three decades of scholarly investigation and innovation, the rich complexity and diversity of American literature written by women can be seen with a new coherence and subtlety. Dedicated to this expanding heterogeneity, The Cambridge History of American Women's Literature develops and challenges historical, cultural, theoretical, even polemical methods, all of which will advance the future study of Americanwomenwriters - from Native Americans to postmodern communities, from individual careers to communities of writers and readers. This volume immerses readers in a new dialogue about the range and depth of women's literature in the United States and allows them to trace the ever-evolving shape of the field'--
Machine generated contents note: Introduction Dale M. Bauer; 1. The stories we tell: American Indian women's writing and the persistence of tradition - Jodi A. Byrd; 2. Women writers and war - Jonathan Vincent; 3. American women's writing in the Colonial period - Kirstin R. Wilcox; 4. Religion, sensibility, and sympathy - Sandra M. Gustafson; 5. Women's writing of the Revolutionary era - Jennifer J. Baker; 6. Women writers and the early US novel - Andy Doolen; 7. Women in literary culture during the long nineteenth century Nancy Glazener; 8. Moral authority as literary property in mid-century print culture -Susan M. Ryan; 9. The shape of Catharine Sedgwick's career - Melissa J. Homestead; 10. Writing, authorship and genius: literary women and modes of literary production - Susan S. Williams; 11. Nineteenth-century American women's poetry: past and prospects - Elizabeth Renker; 12. Transatlantic sympathies and nineteenth-century women's writing - Susan David Bernstein; 13. Nineteenth-century African American women writers - John Ernest; 14. Local knowledge and women's regional writing -Stephanie Foote; 15. Women and children first: female writers of American children's literature - Carol Singley; 16. US suffrage literature - Mary Chapman; 17. American women playwrights - Brenda Murphy; 18. Turn-of-the-twentieth-century transitions: women on the edge of tomorrow - Stephanie Smith; 19. Accidents, agency, and Americn literary naturalism - Jennifer Travis; 20. The geography of ladyhood: racializing the novel of manners - Cherene Sherrard-Johnson; 21. Self-made women: novelists of the 1920s - Jean M. Lutes; 22. Recovering the legacy of Zara Wright and the twentieth-century black woman writer - Rynetta Davis; 23. Jewish American women writers - Hana Wirth-Nesher; 24. Women on the breadlines - John Marsh; 25. Modern domestic realism in America, 1950-1970 - Gordon Hutner; 26. Lyric, gender and subjectivity in modern and contemporary women's poetry - Jennifer Ashton; 27. Contemporary American women's writing: women and violence - Heidi Slettedahl Macpherson; 28. Asian-American women's literature and the promise of committed art - Leslie Bow; 29. Straight sex, queer text: American women novelists - Lynda Zwinger; 30. Latina writers and the usable past - Kimberly O'Neill; 31. Where is she? Women/access/rhetoric - Patricia Bizzell; 32. Reading women in America -Susan M. Griffin; Index.
Includes bibliographical references and index.
Keywords: American literature -- Women authors -- History and criticism; Women and literature -- United States -- History